The Effect of Yaw Angle on a Compressible Rectangular Cavity Flow - Kuan-Huang Lee (International Journal of Aerospace Engineering, 2017)
Experiments are performed to determine the characteristics of a compressible flow over yawed rectangular cavities for Mach numbers of 0.64, 0.70, and 0.83. The cavity’s length-to-depth ratio varies from 4.43 to 21.50 and the length-to-width ratio is unity. The yaw angle is 0°–45°. The upstream compression and downstream expansion near the front and rear corners of a cavity decrease when the value of the yaw angle increases. The amplitude of the fluctuating pressure is a maximum for an open cavity with a yaw angle of 15°. An increase in the yaw angle results in a reduction in the pressure fluctuations for both open and transitional cavities. In the span-wise direction, variations in the mean and fluctuating pressure are less significant than those in the chord-wise direction. The oscillating frequency of resonance varies slightly with the yaw angle, but the amplitudes for the power spectral density are significantly reduced when the yaw angle is larger than 30°. For lower Mach numbers, the lower mode plays an important role in self-sustained oscillations for an open cavity when there is an increase in the yaw angle.